Union by law Filipino American labor activists, rights radicalism, and racial capitalism - McCann, Michael W., 1952- (Chicago series in law and society., 2020)
"Michael McCann and George Lovell offer a history of Filipino salmon cannery workers in Alaska and the Pacific Northwest, focusing on their experiences with law, union organizing, and progressive politics over the course of the 20th century. Coming to this country after the American conquest of the Philippines, many worked at the salmon canneries. The salmon workers were segregated in both the jobs they could have and where they lived. Higher scale jobs were reserved for whites; lower scaled jobs for Filipino workers. Company housing for seasonal workers was also segregated on the same basis. The authors focus on the development of labor unions and fights over the rights of workers to organize effectively during World War II and the Cold War. They argue that economic interests used law to fight the efforts of Filipino workers to organize"--